Cognitive–behavioral treatment of avoidant/restrictive food intake disorder. Issue 6 (November 2018) - Thomas, Jennifer J.; Wons, Olivia B.; Eddy, Kamryn T.
Abstract : Purpose of review: Avoidant/restrictive food intake disorder (ARFID) was added to the psychiatric nomenclature in 2013, but little is known about its optimal treatment. The purpose of this article is to review the recent literature on ARFID treatment and highlight a novel cognitive–behavioral approach, currently under study. Recent findings: The current evidence base for ARFID treatment relies primarily on case reports, case series, and retrospective chart reviews, with only a handful of randomized controlled trials in young children. Studies in adults are lacking. ARFID treatments recently described in the literature include family-based treatment and parent training; cognitive–behavioral approaches; hospital-based re-feeding including tube feeding; and adjunctive pharmacotherapy. A novel form of outpatient cognitive–behavioral therapy for ARFID (CBT-AR) is one treatment currently under study. CBT-AR is appropriate for children, adolescents, and adults ages 10 years and more; proceeds through four stages across 20–30 sessions; and is available in both individual and family-supported versions. Summary: There is no evidence-based psychological treatment suitable for all forms of ARFID at this time. Several groups are currently evaluating the efficacy of new psychological treatments for ARFID – particularly, family-based and cognitive–behavioral approaches – but results have not yet been published.